Une terreur par l’image - Annie DULONG (E-REA)
Contrary to some of the major twentieth century historical events, which required, to be put into fiction, that some blanks were filled – the bombing of Hiroshima and Nagasaki, or the situation in Germany’s concentration camps–, the fictionalization of the September 11th, 2001 events involves not filling the gaps due to a lack of visual archives or a delay in their release, but working with the immediacy and repetitiveness of their omnipresence on television and the Internet. Though this recurrence is truncated, and certain images of the events were omitted (the bodies, for instance), the fact remains that the artists now have to deal with an overflow of images, instead of their elusiveness.This article aims to trace a portrait of the representation of the media in 9/11 novels.  It will focus on novels that address the events head-on, instead of in a minor mode. These novels, aside from the fact that they focus on the events of New York, share a character, or background: the media, represented by television, the internet and press photographs, intervene in the novels in a very significant way, testifying to the sheer force of the images. In studying some of the mechanisms evinced by The Writing on the Wall (Lynne Sharon Schwartz), Extremely Loud and Incredibly Close (Jonathan Safran Foer), Falling Man (Don DeLillo)and A Disorder Peculiar to the Country (Ken Kalfus), this article will offer answers to these questions: what role do the media play, and how do they participate in the narrative? What pressure do the images exercise on the characters? What do the child characters reveal in their relationship to the images? What type of critique of the role played by the media in the trauma of 9/11 are these novels presenting?